In vitro antidiabetic activity of Peperomia pellucida extract and fraction by alpha-amylase inhibition pathway - Sholihatil Hidayati; Shinta Shinta Mayasari; Lindawati Setyaningrum; Ayu Dwi Wardani; Qurrotul Aini (Universitas Ahmad Dahlan, 2022)
The development of type 2 diabetes is influenced by the important role of post-prandial blood glucose management. One strategy in controlling post-prandial hyperglycemia can be done by inhibiting the digestion of dietary carbohydrates through inhibition of alpha amylase enzyme. Natural alpha amylase enzyme inhibition strategy that utilizes natural ingredients is an important alternative in the development of antidiabetic drugs. One of the plants that has the potential to be developed as an antidiabetic is Peperomia pellucida. This study aims to examine the effects of antidiabetic extracts and fractions of Peperomia pellucida in inhibiting alpha amylase enzyme. The research was conducted by determining the total flavonoid using quercetin standard. Antidiabetic studies were carried out by looking at the activity of extracts and fractions of Peperomia pellucida in inhibiting alpha amylase enzyme using visible spectrophotometry method. Data analysis was performed by entering the absorbance value into the standard quercetin curve, while the IC50 value of in vitro antidiabetic activity was determined by entering the value 50 on the curve between the sample concentration and % inhibition of the alpha amylase enzyme. The results showed that the total flavonoid values of the ethanol extract and the ethyl acetate fraction of the herb were 88.24 mg QE/g extract and 80.45 mg QE/g fraction, respectively. Based on the results, the inhibition of alpha amylase enzyme showed that the ethanol extract and the ethyl acetate fraction of the herbs had inhibitory activity with the IC50 value of the ethanol extract 1065.54 g/mL and the ethyl acetate fraction 906.53 g/mL. While the control of acarbose showed an IC50 value of 379.45 g/mL. The ethanol extract and the ethyl acetate fraction of Peperomia pellucida herbs have the potential to be developed as antidiabetic agents with the mechanism of action of inhibiting the activity of the alpha amylase enzyme.